Expression of nestin, CD133 and ABCG2 in relation to the clinical outcome in pediatric sarcomas - Zambo, Iva; Hermanova, Marketa; Zapletalova, Danica; Skoda, Jan; Mudry, Peter; Kyr, Michal; Zitterbart, Karel; Sterba, Jaroslav; Veselska, Renata (Disease markers. Section A, Cancer Biomarkers, 2016)
BACKGROUND: Nestin, CD133 and ABCG2 are recently discussed as putative markers, co-expression of which might determine a cancer stem cell (CSC) phenotype in sarcomas. OBJECTIVE: Our study is focused on immunohistochemical analysis of nestin, CD133 and ABCG2 expression in rhabdomyosarcoma, Ewing sarcoma and osteosarcoma. Furthermore, we also analyzed the possible correlation of nestin, CD133 and ABCG2 expression levels with the patient outcome to identify potential prognostic values of these three putative CSC markers in the same cohorts. METHODS: Using immunohistochemistry, expression of nestin, CD133 and ABCG2 was analyzed in 24 rhabdomyosarcoma, 22 Ewing sarcoma and 10 osteosarcoma tissue samples and expression levels of these markers were correlated with clinical outcome. RESULTS: High nestin levels indicate poor prognosis in patients with Ewing sarcoma (P = 0.001), and high CD133 expression is associated with shorter survival in rhabdomyosarcoma patients (P = 0.002). In contrast, no significant relationship was found between ABCG2 expression and the clinical outcome. CONCLUSIONS: Our analysis represents the first complex study of these three putative CSCs markers together in three different types of pediatric sarcomas and showed their possible prognostic values in these tumors.
Keywords: novorozenec; Infant, Newborn; exprese genu; Infant; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; Gene Expression; kojenec; sarkom; dítě; antigen AC133; Biomarkers, Tumor; Child; Female; mladý dospělý; dospělí; Nestin; lidé; nádorové kmenové buňky; Neoplastic Stem Cells; Immunohistochemistry; imunohistochemie; nádorové biomarkery; předškolní dítě; Adult; Neoplasm Metastasis; Neoplasm Grading; metastázy nádorů; staging nádorů; ženské pohlaví; Kaplanův-Meierův odhad; Sarcoma; Male; Adolescent; nestin; prognóza; stupeň nádoru; Young Adult; Kaplan-Meier Estimate; Neoplasm Staging; mužské pohlaví; Child, Preschool; ABC transportér z rodiny G, člen 2; AC133 Antigen; Prognosis; mladiství